Preoperative Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio for prediction of major complications following Coronary Artery Bypass Grafting - Sina Raeisi; Mohsen Mirmohammadsadeghi; Saba Raeisi; Pouya Mirmohammadsadeghi (ARYA Atherosclerosis, 2023)
INTRODUCTION: The Neutrophil to Lymphocyte Ratio (NLR) and Platelet to Lymphocyte Ratio (PLR) have recently been reported as potentially useful indicators of inflammation. In this study, the authors investigated their predictive role for postoperative complications of Coronary Artery Bypass Graft (CABG).METHOD: This study was conducted on the medical records of patients who had undergone isolated CABG in 2019-2020 in Isfahan, Iran. The baseline clinical characteristics were obtained from medical records. The diagnosis of postoperative Acute Kidney Injury (AKI) was defined based on the Kidney Disease Improving Global Outcomes guideline. The postoperative bleeding amount was measured from the total chest tube output during the Intensive Care Unit (ICU) admission after surgery. NLR and PLR were measured by dividing the neutrophil and platelet counts by the lymphocyte count, respectively. All data were analyzed using the Statistical Package for Social Sciences (SPSS) version 24.RESULTS: Of 356 patients, data of 280 patients, including 219 males and 61 females, were recruited. The mean age among all patients was 63.78±9.07 years. There were no significant differences between the bleeding group and non-bleeding group regarding NLR (2.33(1.89-2.73) vs. 2.20(1.63-3)) and PLR (119.26(94.41-146.39) vs. 110.26(82.13-136.34)) (p=0.742, p=0.228 respectively). NLR and PLR were significantly higher in AKI-positive patients (P< 0.001 and P=0.002, respectively). Only NLR showed the potential ability to predict postoperative AKI in the crude model (P<0.001) based on the regression tests. Moreover, no significant correlation was seen between both NLR and PLR and hospital stay time, ICU stay time, and in-hospital mortality.CONCLUSION: The authors found that an increased NLR is associated with a higher risk for AKI after CABG. The authors also found no significant correlations between NLR and PLR with bleeding, hospital stay, ICU stay, and mortality.